The deficient harvesting rainwater system in Kuala Lumpur and the human-made water pollution conditions - Bonasif, Jorge (International Conference “Environmental Engineering”, 2017)
Rainwater harvesting is a method to collect water from rain, in forms such as direct from the roof, tanks deposits, ponds or artificial lakes. In the city of Kuala Lumpur (1.7 million inhabitants) the process has in consideration flash flood, river pollution, soil erosion. With an annual rainfall of 2486 mm, and build p area reaching 1663.23 km2 in 2014 while forest area has suffered reductions of 8.3% in 2014. The paper examines the conditions that exert pressure in the infrastructure of Kuala Lumpur whose center has experienced an increase in the number of violent flooding yet at the same time prevent an effective harvesting of stormwater. The primary methodology used is consultation of the available literature, journals, published reports, interview with experts and survey at impacted neighbourhoods. A secondary source of information is the observation in situ with a sample case, to help to support the validation of the conclusions. The deficiency in the control of the flooding system in a negative correlation to the city’s development. This fact is related to the insufficient drainage system, narrowed stretches in rivers, low prices of water, and the lack of an adequate incentive policies and low volume of information to the population.